Impacts of the Invasive European Red Ant (Myrmica rubra (L.): Hymenoptera; Formicidae) on a Myrmecochorous System in the Northeastern United States. Issue 4 (16th May 2018) - Gammans, Nicola; Drummond, Frank; Groden, Eleanor
Abstract: We investigated the impact of an invasive ant species from Europe, Myrmica rubra (L.), on a myrmecochorous system (seeds dispersed by ants) in its invaded range in North America. We assessed: 1) how M. rubra process the myrmecochorous diapsores (seeds and elaiosome as a single dispersal unit transported by ants) in comparison with native ants; 2) its preference for common native and invasive diaspore species relative to native ants; 3) how far they disperse diaspores in the field; and 4) the diaspore removal rate by invertebrates and vertebrates in infested areas compared to noninvaded sites. Field experiments demonstrated higher diaspore removal rates over a 10-min and 24-h period by M. rubra compared to native ants. M. rubra's diaspore dispersal distance was 40% greater compared to native ants. In two of three laboratory studies and one field study, there was no significant difference between the seed species which M. rubra and native ants selected. Our data suggest no long-term deleterious effects of M. rubra's invasion on diaspore dispersal in the Maine plant community that is comprised of both native and invasive species. This implies that M. rubra benefits from the myrmechorous plant species' diaspores by increasing their dispersal range away from the parent plant and potentially reducing seed predation. However, it is not known whether the fact that the native ant fauna and M. rubra are attracted to the same plant species' diaspores creates a high level of competition between the ants with deleterious effects on the native ant community.